(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This study analyzes the under-researched yet crucial link between the financial literacy of the population and the country’s acute environmental problems, using Uzbekistan as a case study. While the academic literature increasingly recognizes the link between financial literacy and environmentally responsible behavior, how this relationship manifests in the specific socio-economic context of a country like Uzbekistan, which is transitioning to a “green economy,” remains underexplored. The core problem of the research is that Uzbekistan’s “green” strategies rely heavily on financial instruments (loans, subsidies), but the population’s financial behavior, low trust in the formal financial system, and level of financial literacy may pose a serious obstacle to the effectiveness of this policy. Using a qualitative synthesis methodology of reports from international organizations and existing academic literature, this article reveals the deep gap between the government’s “green finance” policy and the real financial behavior of the population. The main findings show that a large part of the population saves informally, distrust in formal credit is high, and the initial cost of “green” technologies remains a barrier for many, even with subsidies. In conclusion, integrating environmental content into financial literacy programs is not just an additional measure but a fundamental strategic necessity for Uzbekistan to achieve its sustainable development goals. This approach serves to build the knowledge and skills necessary for the population to actively participate not only in their personal financial well-being but also in ensuring the country’s environmental sustainability.